2002
DOI: 10.1002/pon.634
|View full text |Cite
|
Sign up to set email alerts
|

The mental adjustment to cancer (MAC) scale: French replication and assessment of positive and negative adjustment dimensions

Abstract: The Mental Adjustment to Cancer (MAC) scale was validated on a heterogeneous French sample of 317 cancer patients. Internal consistency was satisfactory for the original subscales (alpha coefficients=0.62-0.80), except for the Fatalism subscale (alpha=0.40). The intercorrelations of the subscales and the correlations between the subscales and Anxiety and Depression criteria were congruent with the values reported in the literature. Multidimensional Scaling revealed three positive and three negative subsets of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 29 publications
5
33
1
Order By: Relevance
“…Although the original version of the MAC scale had only been validated in UK population (Watson et al, 1988), it has undergone assessment and validation among patient populations of other ethnicities and countries (Akechi et al, 2000;Cayrou et al, 2003;Ho et al, 2003;Mystakidou et al, 2004). In each case the internal consistency was found to be similar to that of the original version and concurrent validity and correlation was established with other frequently used tools.…”
Section: Methodsmentioning
confidence: 98%
“…Although the original version of the MAC scale had only been validated in UK population (Watson et al, 1988), it has undergone assessment and validation among patient populations of other ethnicities and countries (Akechi et al, 2000;Cayrou et al, 2003;Ho et al, 2003;Mystakidou et al, 2004). In each case the internal consistency was found to be similar to that of the original version and concurrent validity and correlation was established with other frequently used tools.…”
Section: Methodsmentioning
confidence: 98%
“…These findings are coordinate with researches done by Anagnostopoulos et al (23), Grassi et al (29) and Akechi et al (30) that identified helplessness/hopelessness and anxiety preoccupation styles as maladaptive coping styles. Also, it coordinate with Cayrou's study (31) that explains helplessness/hopelessness and anxiety preoccupation as negative coping styles and Kang (9) that suggests the combination of these styles as negative emotion subscales. Given the large role of helplessness/hopelessness coping style in explaining the variance in HRQoL, it can be said that the feeling of helplessness, lack of disease control and knock off the face of the disease play important roles in determining the physical and mental health of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, KoreaneAmericans face cultural and language barriers, which further hinder their ability to access health care and social support sources or providers [3]. Nevertheless, it has been reported that KoreaneAmericans seem to turn to religious beliefs as a new support system; and this may be a venue to retrieve and exchange health information [14].…”
Section: Introduction Q1mentioning
confidence: 99%